Research Progress on Photothermal and Photodynamic Cascade Technology in Food Sterilization and Preservation - LI Jiaqi, YANG Mengfan, LI Tiange, MA Yan, HUANG Xianqing, SONG Lianjun, ZHAO Jiansheng, WANG Tianlin (Shipin Kexue, 2025)
Contamination of foods with foodborne pathogens can cause food spoilage and deterioration, and accidental ingestion may cause bacterial infectious diseases, which not only causes economic loss, but also endangers public health. Unlike traditional sterilization technology, photothermal-photodynamic cascade technology is a technology that kills bacteria by means of thermal energy and reactive oxygen species (ROS) generated by natural substances or highly safe nanomaterials under near infrared irradiation. The combined application of these two technologies significantly extends the shelf-life of fruits and vegetables and delays meat spoilage and deterioration. In addition, this combination has the advantages of high sterilization efficiency while not damaging the flavor or nutritional quality of foods. Therefore, this paper summarizes the mechanism of photothermal and photodynamic sterilization of microorganisms, and the application of photothermal-photodynamic cascade technology in food preservation.